A review of non-specialised, group-based mental health and psychosocial interventions in displaced populations. Issue 3 (10th September 2018) - Wood, Benjamin Mitchell; Kallestrup, Per
Abstract : Purpose: The purpose of this paper is to describe non-specialised, group-based interventions in displaced populations from reviewed literature, and to explore their outcomes. Design/methodology/approach: A literature review was conducted using the PubMed database, Web of Science, The Cochrane Library of Systematic Reviews, and defined "grey literature". Characteristics of the interventions were summarised into a table under key categories such as targeted persons, study setting, level of evidence, outcome measures, assessment tools used and summary of results. Findings: In total, 11 articles were identified stemming from nine separate interventions. Three of these were considered level 1 evidence as they were randomised controlled trials. The described interventions were markedly heterogeneous in nature and produced diverse findings. There were noted methodological issues in the majority of interventions reviewed. Originality/value: This original research has demonstrated clear need for research that uses robust methodology accounting for the complex and challenging nature of this context.